Extracts From Red Eggplant: Impact of Ohmic Heating and Different Extraction Solvents on the Chemical Profile and Bioactivity - Ferreira-Santos, Pedro; Duca, Anna Barbara; Genisheva, Zlatina; Silva, Beatriz Nunes; De Biasio, Filomena; Botelho, Cláudia; Rocha, Cristina M. R.; Gorgoglione, Domenico; Teixeira, José A. (Frontiers in Sustainable Food Systems, 2021)
Eggplants contain a multitude of biocompounds with nutritional and/or biological activities. The objective of this work was to study the nutritional, chemical and bioactive value of red eggplant from Rotonda, Italy. Ohmic heating (OH) was compared to conventional heating, as different solvents were used (water, ethanol 30, 50, and 90% and methanol) for biocompounds extraction. Extracts were evaluated for their total phenolic compounds, antioxidant and antibacterial activities, and its toxicity was assessed in cells, L929 and Caco-2. The nutritional characterization of Rotonda's eggplant demonstrated that it is rich in carbohydrates (65%), fiber (12.5%), proteins (13%), lipids (7.6%) and minerals. Potassium is the mineral with the highest concentration in the red eggplant (27.24 mg/g). Phenolic composition of the obtained extracts was dependent on the extraction method, as well as on the solvent. The use of OH method increased the extraction of biocompounds, especially when using 50% of ethanol as solvent. The main phenolic compounds found in the extracts of this eggplant variety were ellagic acid, p-coumaricic acid, epicatechin, narginin, taxifolin and kaempferol. Antioxidant activity was positively correlated with the total amounts of phenolics. Red Eggplant extracts showed activity against Gram-negative bacteria (E. coli and S. enterica), however, they did not demonstrate activity against Gram-positive bacteria. The extracts obtained did not show cytotoxic effects in fibroblast and colorectal studied cells. Ohmic heating is a sustainable technology that increases the extraction yield of biocompounds, with reduced energy consumption and the resulting extracts show low toxicity and high biological activity.